ANALISIS KOMPARATIF ANTARA BAHASA JAMEE (ACEH) DAN BAHASA MINANGKABAU (BUKITTINGGI) - NFN Ramli; Novia Erwandi (Masyarakat Linguistik Indonesia, 2019)
The problems in this study are the differences in phonology, lexical, morphology, and syntactic structure between Jamee (Aceh) and Minangkabau (Bukittinggi). The aim of this research is to know the difference of phonology, lexical, morphology, and syntactic structure between Jamee language and Minangkabau Bukittinggi language. The method used in this research was descriptive with qualitative approach. Data were collected by observation, interview, and documentation techniques. The data sources in this research were 5 speakers of Jamee language and 5 speakers of Minangkabau Bukittingi language. the data analysis procedures were data selection, data classification, and data presentation. The results of research in this article phonological differences, there were / ɛ / and / ɔ / in vocal system of Jamee, / a / while vocal system of Minangkabau Bukittinggi language and Jamee / ɣ / or / R / language consonant system, while Minangkabau Bukittinggi language / r /, then there were pronunciation differences include single vowels, double vowels, and consonants. These differences consist of nouns, adjectives, verbs, and adverbs. For affixation, the difference lies in the insertion (infix) -al-, -ar- in Jamee and -am-, -um- in Minangkabau Bukittinggi. The suffixes (suffixes) -en, -ken in Jamee, -in the Minangkabau language of Bukittinggi, and the ends (confix) there were me-ken, me-en, ma-kan, ma-an in Minangkabau language Bukittinggi, except prefixes. The prefixes of the two languages have similarity. The differences was also seen from word classification in verbs, nouns, adjectives, numerelia, and adverbs. In terms of the type of word repetition there was no difference only in the form of words or basic words only, while the sentence structure of the two languages have in similarities.